The Global Gender Distortions Index (GGDI) - Pinelopi Goldberg; Charles Gottlieb; Somik Lall; Meet Mehta; Michael Peters; Aishwarya Lakshimi Ratan (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
The extent to which women participate in the labor market varies greatly across the globe. If such differences reflect distortions that women face in accessing good jobs, they can reduce economic activity through a misallocation of talent. In this paper, we build on Hsieh et al. (2019) to provide a methodology to quantify these productivity consequences. The index we propose, the "Global Gender Distortions Index (GGDI)", measures the losses in aggregate productivity that gender-based misallocation imposes. Our index allows us to separately identify labor demand distortions (e.g., discrimination in hiring for formal jobs) from labor supply distortions (e.g., frictions that discourage women's labor force participation) and can be computed using data on labor income and job types. Our methodology also highlights an important distinction between welfare-relevant misallocation and the consequences on aggregate GDP if misallocation arises between market work and non-market activities. To showcase the versatility of our index, we analyze gender misallocation within countries over time, across countries over the development spectrum, and across local labor markets within countries. We find that misallocation is substantial and that demand distortions account for most of the productivity losses.
Keywords: O4; O11; J16; J20; 330; misallocation; gender gaps; economic growth; development; discrimination